Comparison of presentation and performance status between cancer patients residing in rural and urban areas of Punjab, Pakistan - Ali, Muhammad Mohsin (International Journal of Pathology, 2023)
Background: Cancer has a diverse presentation in the population which may be affected by factors such as equity of healthcare access, distance from cancer care centers, and affordability of cancer treatment. This study aimed to record disparities among the stage of presentation and performance status in patients presenting to a tertiary care cancer center from rural and urban backgrounds.Methods: An observational cross-sectional study was carried out at a tertiary care cancer center from September 2019 to August 2020. Two hundred and ninety-five patients from both urban and rural areas were included. Patient characteristics were recorded using an interview-based questionnaire and ECOG performance scale, and were similar in both groups. Statistical Analysis: Data analysis was performed using SPSS 24.0, with qualitative statistics determined as frequency and percentages, and quantitative correlations among variables determined by application of a chi-square test with p-value ≤ 0.05 as significant.Results: In this study, 150 (50.8%) of the participants were female; 52.9% were from urban areas. A significant proportion of the patients had either stage III (20.3%) or stage IV (60%) disease on presentation. More than 50% of the patients had an ECOG performance status score of either 3 (36.9%) or 4 (20%) on presentation or during admission. No significant associations were present between location as urban or rural and stage of cancer (ρ=0.076, p=0.194), or between location and ECOG score (ρ=-0.033, p=0.573).Conclusion: Many of the determinants of late cancer presentation are similar among urban and rural areas, and patient education, mass screening programs, and the involvement of primary care physicians in cancer care can play an effective role in subverting this problem.